ROBOT PENGANTAR BARANG OTOMATIS BERBASIS MIKROKONTROLER AVR ATMEGA16 - Prawiroredjo, Kiki; Iriyanto, Iriyanto (Jurnal Teknik Elektro, 2008)
Automatic Object Delivery Robot Based on AVR ATMega16 Microcontroller is a robot thatdelivers goods to a certain location and move back to its initial position automatically, andavoids obstacles to reach any location. This Robot is built by using two stepper motors formoving forward and backward, and SHARP GP2D12 infra red sensor connectedmechanically to the servo motor in order to turn the sensor around 45 degrees to detect theexistence of any obstacle at a certain distance around the robot. Transmitter in the sensorwill transmit infra red light and if there are obstacles at a distance of 10 to 36.7 cm, the infrared light will be reflected to the sensor. AVR ATMega16 Microcontroller as the processorwill analyze the area of the obstacles at certain distance and move the robot to the areawhere there is no obstacle. After being assembled and tested, this robot can go to itsdestination and back to its initial position as programmed. There are errors as the robotreaches its destination. For example, the destination coordinate is x=2 and y=6 becomesx=1,95 and y=6, and the initial position coordinate is x=2 and y=0 becomes x=1,7 andy=0 when tested without obstacles, and the coordinate becomes x=1,4 and y=0 when testedwith obstacles. These errors occur due to inaccuracy of stepper motor rotation.Keywords: Robot, Microcontroller, stepper motor, servo motor, infrared sensor.